PERAN PERANGKAT DESA DALAM AKUNTABILITAS PENGELOLAAN DANA DESA (STUDI KASUS DESA SELEMAK KECAMATAN HAMPARAN PERAK KABUPATEN DELI SERDANG) - Sianipar, Zefanya Putri; Saribu, Ardin Dolok; S Sihombing, Halomoan (JURNAL LENTERA AKUNTANSI, 2025)
This study aims to determine the role of village officials in the accountability of village fund management in Selemak Village, Hamparan Perak District, Deli Serdang Regency. This study aims to determine whether the role of village officials in the accountability of village fund management in Selemak Village, Hamparan Perak District, Deli Serdang Regency complies with Minister of Home Affairs Regulation No. 20 of 2018, which outlines the stages of village fund management, including planning, implementation, administration, reporting, and accountability. It also emphasizes principles of village fund management, such as transparency, participation, accountability, and budgetary discipline. This study employed a qualitative descriptive approach with a case study approach. The data collected consisted of primary and secondary data, obtained through interviews and documents documenting village fund management budget realization reports. Source triangulation was used to analyze data validity. The data analysis technique employed in this study was narrative analysis. The results of this study indicate that the Village Officials in Selemak Village have played a positive role in the accountability of village fund management stages, starting from the planning process, implementation, administration, reporting, and accountability, carried out in accordance with their respective responsibilities. However, in terms of transparency, the Selemak Village Officials have played a less effective role because the realization report has not been announced in detail and in its entirety to the Selemak Village community on the billboards located in the Selemak Village Office